2020
DOI: 10.1186/s12882-020-02193-x
|View full text |Cite
|
Sign up to set email alerts
|

Time changes in the spectrum of urinary stone composition: a role for climate variations?

Abstract: Background An increase of the frequency of uric acid urinary stones compared to calcium-containing ones has been recently described. This study was aimed at assessing the frequency of different types of urinary stones in the population of northern Italy in the period 2016–18 compared to 2001–2003. Methods Analyses by infrared spectroscopy of 1007 stones endoscopically removed at two institutions in the area of Milan (Northern Italy) were retrospect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Uric acid stones have increased in men, whereas carbonate apatite stones have decreased significantly in women in the same cohort [27 ▪ ]. Inversely, no significant rise in uric acid stones was observed in a study conducted in Italy [24]. Also, in Turkey, calcium oxalate (CaOx) stones have markedly increased from 2006 to 2019 [19].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Uric acid stones have increased in men, whereas carbonate apatite stones have decreased significantly in women in the same cohort [27 ▪ ]. Inversely, no significant rise in uric acid stones was observed in a study conducted in Italy [24]. Also, in Turkey, calcium oxalate (CaOx) stones have markedly increased from 2006 to 2019 [19].…”
Section: Resultsmentioning
confidence: 98%
“…Table 1 summarizes the findings of the studies that met our inclusion criteria. Twenty-three studies were identified reporting on urolithiasis epidemiology, prevalence, and trends from 11 different countries in the past 2 years [6 ▪▪ ,12,13 ▪ ,14 ▪ ,15,16 ▪▪ ,17,18 ▪ ,19–26,27 ▪ ,28–33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the prevalence of stone disease rises worldwide and a growing number of patients will need a minimally invasive procedure to treat kidney stones [ 29 ]; second, recurrent urinary tract infections and related antibiotic treatment are frequent and serious issues in the everyday clinical practice, thus predisposing patients to further infective danger [ 30 , 31 ]; third, also connected to the previous observation, the rate of infected stones (e.g. struvite) in increasing, at least in Western countries [ 32 ]; forth, continued improvements in life expectancy have seen the growth of the elderly population, with associated chronic diseases (e.g. diabetes mellitus, immune disorders) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of urinary stones increased from 1986 to 1998 by 40% in males and by 20% in females (10). From 2001-2003 to 2016-18, the mean age of patients increased from 45.8+/-15.4 years to 57.9+/-14.8 years and the frequency of calcium oxalate monohydrate stones increased from 44 to 51% (21). From 1986-1998 to 2005-2010, a change of the urinary biochemical characteristics of renal stone formers patients in Italy was observed.…”
Section: Introductionmentioning
confidence: 98%